Assessment of Serum and Salivary Vitamin E Levels in Oral Potentially Malignant Disorders and Oral Cancer - Bhat, Supriya; Babu, Subhas; Kumari, Suchetha; Shetty, Shishir Ram; Kamath, Vinayak; Bhat, Saidath; Areekat, Fazil K; Madi, Medhini; Achalli, Sonika; Madiyal, Ananya (UI Scholars Hub, 2018)
An increase in lipid peroxidation and a decrease in antioxidant activity have been reported in patients with cancer in comparison with normal subjects. Objective: To estimate the status of serum and saliva by assessing the serum and salivary vitamin E levels in patients with oral potentially malignant disorders and oral cancer. Methods: A total of 90 participants were enrolled in this study. 30 subjects with oral potentially malignant disorders, 30 sub¬jects with oral cancer, and 30 healthy subjects (controls). Serum and saliva samples were collected and vitamin E levels were assessed. The data were analyzed using ANOVA for between-group comparison. Post hoc Tukey analysis was used for comparing the two study groups with the control group. Pearson correlation coefficient was used to determine concordance between the groups. Results: Mean vitamin E levels in serum and saliva were sig¬nificantly decreased in oral potentially malignant disorders and oral cancer compared with controls. Conclusion: As significant reduction in vitamin E levels was observed in saliva, it was evident that salivary vitamin E levels potentially be used as a reliable, non invasive biomarker for diagnosing and managing oral potentially malignant disorders and oral cancer.